A computational model for dynamics in effective usage of ICT public access centre - Yusop, Nor Iadah; Ahmad, Faudziah; Mat Aji, Zahurin; Ab. Aziz, Azizi (Asian Research Publishing Network (ARPN), 2015)
In Malaysia, ICTs have been identified as a crucial enabler in the knowledge-based economy to facilitate the acquisition, utilization, and dissemination of knowledge towards enhancing the economic and social values of society.Numerous programmes have been organized, developed, designed and executed to optimize the usage of these ICT Public access centres (telecentres). This paper presents a computational model that addresses important factors contributing to the effective usage of telecentres. Simulation was used to show the behaviors produced by the model. Several cases of different scenarios showed various patterns that are consistent with past literatures. These results indicate that the model is able to illustrate different behaviors when different scenarios are applied.The model could be used as a justification for conducting an inception study to understand the working model of a telecentre’s operation given a certain scenario.